Development and Characterization of Clopidogrel-loaded Ethosomal Transdermal Patch for Antiplatelet Effect - Mishra, Subhendu S. (Asian Journal of Pharmaceutics (AJP), 2016)
Aim: Clopidogrel is an oral, thienopyridine-class antiplatelet agent used to inhibit blood clots in the condition of different artery and vascular disease and prevent the chances of myocardial infarction and stroke. Since oral bioavailability of clopidogrel is poor due to high first-pass metabolism (only 15% metabolite in active form), to increase the bioavailability, different matrix-type transdermal patches containing clopidogrel-loaded ethosomes were formulated in this work to release and absorb the drugs direct systemic circulation. Materials and Methods: Ethosomes prepared by hot method were characterized for size, surface charge, and entrapment efficiency. Result and Discussion: Ethosomes were characterized for size, surface charge, and entrapment efficiency which were 112.87 ± 1.90 nm, −17.4 ± 1.02, and 71.48 ± 4.23%, respectively. The polymers selected for preparation of ethosomes containing transdermal patches were polyvinyl alcohol, polyvinylpyrrolidone, and polyethylene glycol-4000 in different concentration ratios. The patches were evaluated for thickness, weight uniformity, drug content, moisture content, and uptake and found a significant result. Transmission electron microscopy analysis shows that the prepared ethosomes have the suitable diameter and spherical in shape. All the films were found to be stable at room temperature and accelerated temperature condition in respect to their physical parameters and drug content. In vitro drug release study after 72 h was found to be 57.39% ± 0.17%. Conclusion: This work may conclude that the prepared transdermal patches were stable and can be used to drug delivery application.